2015
DOI: 10.1371/journal.pone.0117273
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic and Mutation-Based Suppression of a Berberine Bridge Enzyme-Like (BBL) Gene Family Reduces Alkaloid Content in Field-Grown Tobacco

Abstract: Motivation exists to develop tobacco cultivars with reduced nicotine content for the purpose of facilitating compliance with expected tobacco product regulations that could mandate the lowering of nicotine levels per se, or the reduction of carcinogenic alkaloid-derived tobacco specific nitrosamines (TSNAs). A berberine bridge enzyme-like (BBL) gene family was recently characterized for N. tabacum and found to catalyze one of the final steps in pyridine alkaloid synthesis for this species. Because this gene fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
82
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(90 citation statements)
references
References 50 publications
7
82
1
Order By: Relevance
“…Although nicotine accumulation in tobacco should be considered a quantitative trait controlled by numerous genes and highly influenced by the environment, several large‐effect loci have been identified that might be used to reduce nicotine content. First, recessive alleles at the Nic1 and Nic2 (also designated as A and B ) loci have been transferred from cigar to flue‐cured tobacco to reduce nicotine levels to approximately 2 to 4 g kg −1 (Chaplin and Weeks, 1976; Lewis, 2018; Lewis et al, 2015). This variability has been associated with reduced cured leaf yields and quality, however, and no flue‐cured cultivar containing this genetic variability is widely grown commercially at the current time.…”
Section: Influence Of Variety Choice and Plant Geneticsmentioning
confidence: 99%
“…Although nicotine accumulation in tobacco should be considered a quantitative trait controlled by numerous genes and highly influenced by the environment, several large‐effect loci have been identified that might be used to reduce nicotine content. First, recessive alleles at the Nic1 and Nic2 (also designated as A and B ) loci have been transferred from cigar to flue‐cured tobacco to reduce nicotine levels to approximately 2 to 4 g kg −1 (Chaplin and Weeks, 1976; Lewis, 2018; Lewis et al, 2015). This variability has been associated with reduced cured leaf yields and quality, however, and no flue‐cured cultivar containing this genetic variability is widely grown commercially at the current time.…”
Section: Influence Of Variety Choice and Plant Geneticsmentioning
confidence: 99%
“…An extremely weak "nicotine synthase" has been reported (6), but other authors could not repeat this finding (5). Although it has been suggested that this is possibly catalyzed by an enzyme of the berberine-bridge type (7), no details of the nature of this key enzyme nor of its mechanism are available.…”
mentioning
confidence: 98%
“…The isoflavone reductase-like enzyme A622 and a berberine bridgelike (BBL) enzyme are proposed to be involved in the condensation step of the pyridine and pyrrolidine rings to form nicotine (DeBoer, Lye, Aitken, Su, & Hamill, 2009;Kajikawa, Hirai, & Hashimoto, 2009). The synthesis and accumulation of the major and minor alkaloids is closely related and dynamically regulated (Chintapakorn & Hamill, 2003;Hung et al, 2013;Kajikawa et al, 2009;Lewis et al, 2015).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…The isoflavone reductase-like enzyme A622 and a berberine bridgelike (BBL) enzyme are proposed to be involved in the condensation step of the pyridine and pyrrolidine rings to form nicotine (DeBoer, Lye, Aitken, Su, & Hamill, 2009;Kajikawa, Hirai, & Hashimoto, 2009). The synthesis and accumulation of the major and minor alkaloids is closely related and dynamically regulated (Chintapakorn & Hamill, 2003;Hung et al, 2013;Kajikawa et al, 2009;Lewis et al, 2015).Previous research indicates that many factors affect nicotine biosynthesis, including mechanical wounding, topping (decapitation of the apical meristem), plant hormones, transcription factors, and negative feedback by pathway products (Baldwin, Schmelz, & Ohnmeiss, 1994;Elliot, 1966;Wasternack & Hause, 2013) In this study, we intended to gain more insights on JA regulated nicotine synthesis in tobacco by modifying expression of the JA biosynthetic genes. As we do not know which enzyme controls the rate-limiting step of JA biosynthesis, we investigated all five major genes in the pathway.…”
mentioning
confidence: 99%